Comparative succession law. Volume II, Intestate succession - Reid, Kenneth (Kenneth G. C.); De Waal, M. J. (Marius Johannes); Zimmermann, Reinhard, 1952 October 10- (Oxford : Oxford University Press, 2015)
Exploring the rules that apply when a person dies without leaving a valid will, 'Intestate Succession' delivers a comparative and historical review of the relevant law in Europe and beyond, including an analysis of legal development, justifications, and reform.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 9, 2015).
Keywords: Inheritance and succession; Comparative law